MODEL KONSELING RESOLUSI KONFLIK BERLATAR BIMBINGAN KOMPREHENSIF UNTUK MENGEMBANGKAN KOMPETENSI HIDUP DAMAI DAN HARMONI SISWA SMK - Sudrajat, Dadang; -, Ilfiandra; Saripah, Ipah (Universitas Pendidikan Indonesia, 2015)
This study aimed at formulating a model of conflict-resolution counseling with comprehensive guidance ground for developing peace and harmony life competences of vocational high school students. Quantitative-qualitative approach with researchand development method was used. Population of the research consisted of students of vocational high schools in Bandung Municipality with its sample amounting to 364 students, 4 counselors, and 1 expert of guidance and counseling intervention. Results showed: (1) learning to be and learning to live together were education pillars which were not neglected, where there is a view that learning to live together as a parexcellent pillar; (2) Generally students’ peace and harmony life competences were in high category but affection, harmony, and thanks giving aspects needed to be developed; (3) conflict resolution was under the umbrella of peace education, in agroup with peace, reconciliation, tolerance, respect to human rights, and civil participation; (4) based on theoretical and empirical consideration, the conflict - resolution guidance with comprehensive guidance background was predicted to beable to become an alternative solution for developing students’ peace and harmony life competences, and (5) validation results of a rational model that involved guidance and counseling experts and school counselors showed that the model had feasibility to be implemented at school.Keywords: counseling, conflict-resolution, comprehensive guidance, peace and harmony life.